Efficient butanol bioproduction from renewable lignocellulosic biomass by an integrated strategy of ternary deep eutectic solvent pretreatment and clostridial fermentation: toward complete utilization of reed straw - Shao, Yu; Zhang, Cheng; Wang, Jiabin; Xie, Fang; Wang, Shijie; Yang, Rongling; Luo, Hongzhen (Frontiers in Microbiology, 2025)
The main route for biobutanol production is anaerobic clostridial fermentation using corn and sugarcane as substrates. The high-price of raw materials in above processes largely limits its application as an advanced biofuel. The renewable lignocellulosic biomass is an ideal feedstock to produce butanol. However, the structure of lignocellulose is complicated which needs pretreatment to facilitate enzymatic efficiency and substrate fermentability. Herein, the green ternary deep eutectic solvent (DES) composed of choline chloride, succinic acid, and glycerol was synthesized. To improve DES pretreatment performance and reduce the viscosity of reaction system, water was added as co-solvent. Results indicate that xylan removal and glucan recovery were 61.7% and 93.6% when pretreating reed straw (RS) by DES/H2O (80:20, wt%) at 120 °C for 4 h. In this case, glucose yield reached 87.9% by cellulase after 72 h enzymolysis, which is 6.2-fold to untreated RS. Afterward, saccharification yield of treated reed was further elevated to 93.1% assisted by Tween 80 (100 mg/g-substrate). The reed hydrolysate was then applied as substrate for biobutanol production by Clostridium acetobutylicum ATCC 824, and approximately 6.5 g/L butanol and 8.8 g/L total solvents was obtained from the real hydrolysate. Finally, the enzymatic residues of reed were prepared to porous hydrochar materials via hydrothermal carbonization at 220 °C for 8 h. Adding 2.0 g/L hydrochar was verified for enhancing butanol titer to 11.5 g/L from synthetic medium containing typical pretreatment-derived inhibitors. In summary, this study provides an efficient butanol bioproduction route integrated with the complete valorization of renewable lignocellulosic biomass.